Answer:
Step-by-step explanation:
Solution by substitution method
3x+5y=7
and 4x-y=5
Suppose,
3x+5y=7→(1)
and 4x-y=5→(2)
Taking equation (2), we have
4x-y=5
⇒y=4x-5→(3)
Putting y=4x-5 in equation (1), we get
3x+5y=7
⇒3x+5(4x-5)=7
⇒3x+20x-25=7
⇒23x-25=7
⇒23x=7+25
⇒23x=32
⇒x=32/23
→(4)
Now, Putting x=32/23
in equation (3), we get
y=4x-5
⇒y=4(32/23)-5
⇒y=(128-115)/23
⇒y=13/23
∴y=13/23 and x=32/23
8x - y = 54
8x + 2y = 60
subtracting, we get -3y = -6
y = 2
x = 7
Answer is (c) (7,2)
Your proof is correct and very well done
Answer: 3.5, 4.5, 9.5, 3.5
Step-by-step explanation:
Look at the image below to see where A, B, C, and D are.
A + B = 8
B + D = 8
A + C = 13
C - D = 6
we can see that A + B = 8 and D + B = 8, so A = D
substitute this into A + C = 13 to get D + C = 13
from D + C = 13 we can get D = 13 - C
plug this into C - D = 6 to get C - (13 - C) = 6
2C - 13 = 6
2C = 19
C = 9.5
Now we can find D = 13 - C = 13 - 9.5 = 3.5
D = 3.5
Now we can find A = D = 3.5
A = 3.5
Now we can find B from A + B = 8
B = 8 - A = 8 - 4.5 = 4.5
B = 4.5
Answer:
45 DOLLARS
Step-by-step explanation:
For these kind of problems, write an equation to figure out the answer.
55 + 2x = 145
x represents the bag cost
145 is the shoe cost
Take out the constant, which is 55, from both sides. A constant is a useful term you should learn.
The result is: 2x = 90
Divide 2x by 2, to get x, which is the bag cost, by itself.
Result: x= 45
Since x is the bag cost, the bag costs 45 dollars
Please mark me brainliest